2015
DOI: 10.1002/sat.1126
|View full text |Cite
|
Sign up to set email alerts
|

A method to achieve clear-sky data-volume download in satellite links affected by tropospheric attenuation

Abstract: SUMMARYFor data downloading from satellites, the traditional approach of considering the complementary probability distribution, P(A trop ) of the total tropospheric attenuation A trop (dB), at a frequency, polarization, and elevation angle, may be too pessimistic, and it may lead to large overdesign. If the data volume downloaded in a given observation time T obs (a day, a week, a month, etc.), with a constant probability of symbol error, is more valuable than the instantaneous symbol, or bit rate (as it may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…delivering data with the mininum tolerated probability of symbol error. In [10], we have shown that in data channels this approach is too pessimistic and leads to large overdesign.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…delivering data with the mininum tolerated probability of symbol error. In [10], we have shown that in data channels this approach is too pessimistic and leads to large overdesign.…”
Section: Introductionmentioning
confidence: 99%
“…If the data volume downloadable during rainfall, with a constant probability of symbol error, is more valuable than the instantaneous symbol rate -e.g. in remote sensing and internet of things (IoT) using satellites -the method discussed in [10] can avoid overdesign. This method is usefull when: (a) data must be downloaded also when it is raining (e.g., because of satellite pass, or other technical or service constraints); (b) real-time communication is not strictly required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to increase the provided data rates in an efficient, cost-effective manner and taking into consideration the spectrum scarcity problem [5,6], next generation satellite communication systems are migrating to the Ka and Q/V bands and are expected to make extensive use of link adaptation strategies combined with multi-beam satellites and/or other relevant techniques [7][8][9][10][11][12][13][14]. Signal propagation at Ka-band frequencies and above is, nevertheless, highly affected by the various atmospheric phenomena causing degradation of the overall system performance.…”
Section: Introductionmentioning
confidence: 99%